1995
DOI: 10.1210/jcem.80.5.7745001
|View full text |Cite
|
Sign up to set email alerts
|

Multihormonal regulation of progesterone synthesis in cultured human midluteal cells.

Abstract: The objectives of this investigation were to examine in vivo insulin like-growth factor-I (IGF-I) secretion by the human midcorpora lutea (mid-CL) and the effects of IGF-I, hCG, FSH, and human GH on progesterone (P) production by CL cells obtained from patients at laparotomy. We first examined whether the CL produces IGF-I by measuring IGF-I levels in the ovarian vein from the ovary bearing the CL. The IGF-I concentration in the ovarian vein bearing the CL (206 +/- 31 ng/mL) was significantly increased compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…Functional studies have shown that IGF-I stimulates progesterone production by the rat corpus luteum (Parmer et al, 1991), which increases when the cells are stimulated simultaneously with IGF-I and hCG (Talavera and Menon, 1991). Similar results have been reported in human luteal cells, in which IGF-I enhances both basal and hCG-stimulated progesterone production (Devoto et al, 1995). In addition, IGF-I induces an increase in oestradiol secretion by human luteinized granulosa cells and by luteal cells in culture (Erickson et al, 1989;Johnson et al, 1996).…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Functional studies have shown that IGF-I stimulates progesterone production by the rat corpus luteum (Parmer et al, 1991), which increases when the cells are stimulated simultaneously with IGF-I and hCG (Talavera and Menon, 1991). Similar results have been reported in human luteal cells, in which IGF-I enhances both basal and hCG-stimulated progesterone production (Devoto et al, 1995). In addition, IGF-I induces an increase in oestradiol secretion by human luteinized granulosa cells and by luteal cells in culture (Erickson et al, 1989;Johnson et al, 1996).…”
Section: Introductionsupporting
confidence: 76%
“…Tissue explants (three corpora lutea from the early luteal phase, n = 8 slices; five corpora lutea from the mid-luteal phase, n = 12 slices; and four corpora lutea from the late luteal phase, n = 10 slices) were treated with L-Arginine (1 mmol l -1 ) forIGF receptor was not addressed directly in the present study, although the data indicate that the binding proteins and the receptor regulate the metabolic actions of IGFs in corpora lutea from the mid-luteal phase. IGF-I exerts a luteotrophic action by stimulating progesterone and oestradiol synthesis in cultures of luteal cells from the midluteal phase (Devoto et al, 1995;Niswender et al, 2000).…”
Section: Fig 3 Effect Of Nitric Oxide On (A) Insulin-like Growth Famentioning
confidence: 99%
“…Using human luteal cells from early and mid-luteal phase of the menstrual cycle, Apa et al (1996) found that IFG-I was able to stimulate directly production of progesterone and additionally mediated the positive action of GH on progesterone synthesis. Measuring IGF-I production by the CL and then synergistic action with GH, FSH and hCG on progesterone secretion, Devoto et al (1995) suggested that human CL is a site of secretion, action and reception of IGF-I during the mid-luteal phase.…”
mentioning
confidence: 99%
“…Three women undergoing tubal ligation were administered Cetrorelix (2 mg, sc; ASTA Medica AWD GmnH, Frankfurt, Germany) during the midluteal phase 24 h before surgery. Plasma LH and progesterone were determined by specific RIA as previously reported (5). These studies were approved by the internal review board of the Hospital Clinico San Borja Arriarán.…”
Section: Subjects and Methods Subjectsmentioning
confidence: 99%